Konsep OOP pada Pemrograman Visual Basic - Sri Eniyati; Rina Candra Noor Santi (Dinamik, 2003)
Object-Oriented Programming is innovation in development for software the last decade, moreover to appear visual programming language models. OOP concept needed for implementation components used in application preparation and preparation new component, so that to appear visual programming language models, preparation new component in veil VB programming is news interesting, except for to fill requisites unique new component, so using plentiful OOP concept.